Does human capital spillover affect labor productivity? - Laut, Lorentino Togar; Pranizty, Tasya Putri Indra; Sugiharti, Rr Retno (Publisher of Widyagama University of Malang (UWG Press), 2023)
As a developing country, in 2022 Indonesia is the 4th largest population in the world and predicted to experience a demographic bonus in 2020-2035. However, along with the increase in the population and workforce in Indonesia, it turns out that the productivity of the workforce in Indonesia is still low. This study aims to analyze and examine the effect human capital spillovers proxied by higher educated labor and lifetime in-migration on labor productivity in Indonesia along with other production factor variables. This study used panel data collected from 28 provinces in Indonesia in period of 2010 to 2019. Based on the results, the higher the level of education, the higher the productivity and the presence of higher educated labor can provide knowledge spillover for the environment. Meanwhile, human capital spillover from indicators in-migration has no impact on productivity. These results indicate that knowledge spillover support by quality of human capital, but the movement of labor has not provided positive externalities for the surrounding environment.JEL Classification E24; J24; O47